TAFSIR KONTEMPORER ATAS “AYAT PERANG” Q.S. AL-TAUBAH (9): 5-6: PERSPEKTIF HERMENEUTIKA JORGE J.E. GRACIA - Ulummudin Ulummudin (Aqlam: Journal of Islam and Plurality, 2019)
AbstractThis paper focuses on Q.S. al-Taubah (9): 5-6 often used as a justification of violence in the name of religion. The author argues a comprehensive understanding is needed to better understand these verses, exploring the meaning of the verses through Gracia’s method of hermeneutics. The method utilizes both textual and non-textual perspective in reading the verses. Textual perspective implies using three function, namely historical, meaning, and implicative function. The non-textual perspective involves historical, political, psychological approach, etc. Historical function of these verses is related to Hudaibiyah agreement which was violated by people of Quraisy in Mecca, leading to conflict and war situation. Meanwhile, its meaningful function could possibly tell us that war is the last option to end the chaos for the sake of peace and freedom of expression. Next, the verses implicative function is to keep a peace among human being regardless of their ethnic, culture, and religion. Meanwhile, non-textual perspective for Indonesian context is an advice to obey and be loyal toward Pancasila. Refusing Pancasila as a principle of Indonesia is deemed as destroying the agreement which has been signed.Key Words: Interpretation; war verses; Gracia’s Hermeneutics. AbstrakTulisan ini mengkaji tentang Q.S. al-Taubah (9): 5-6. Ayat ini sering digunakan sebagai justifikasi terhadap kekerasan atas nama agama, sehingga diperlukan pemahaman yang memadai. Metode yang digunakan untuk memahaminya adalah hermeneutika Gracia. Metode tersebut meniscayakan adanya pembacaan tekstual dan non-tekstual. Pembacaan tekstual dapat dilakukan melalui penjelasan terhadap tiga fungsi yakni historis, makna, dan implikasi, sedangkan non-tekstual dapat melibatkan pendekatan sejarah, politik, psikologi, dll. Analisis fungsi historis ayat ini berkaitan dengan perjanjian Hudaibiyah yang dilanggar oleh kaum musyrikin Quraish Mekah, sehingga situasi kembali ke dalam peperangan. Sementara, fungsi maknanya adalah perang sebagai jalan terakhir untuk mengatasi kekacauan demi meraih kedamaian dan kebebasan berekspresi. Selanjutnya, fungsi implikasinya ialah kewajiban untuk hidup rukun dan menjaga perdamaian antar manusia walaupun berbeda etnis, budaya, dan agama. Sementara itu, untuk pembacaan non tekstual dalam konteks keindonesiaan, ayat ini memberikan himbauan untuk setia terhadap Pancasila. Penolakan terhadap Pancasila berarti melanggar perjanjian yang telah disepakati.Kata Kunci : Tafsir; ayat perang; hermeneutika Gracia.